If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2n = 2 + 3n Solving 3 + -2n = 2 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 3 + -2n + -3n = 2 + 3n + -3n Combine like terms: -2n + -3n = -5n 3 + -5n = 2 + 3n + -3n Combine like terms: 3n + -3n = 0 3 + -5n = 2 + 0 3 + -5n = 2 Add '-3' to each side of the equation. 3 + -3 + -5n = 2 + -3 Combine like terms: 3 + -3 = 0 0 + -5n = 2 + -3 -5n = 2 + -3 Combine like terms: 2 + -3 = -1 -5n = -1 Divide each side by '-5'. n = 0.2 Simplifying n = 0.2
| 4x^2+10x+6=2x^2+6x+4 | | 6(2x+7)+3(x-10)= | | 16-2m=5m+8 | | 7-3[x+2]=4 | | 7x+x=4 | | x^3+5x^2+3x=0 | | 76=-3x+2(6x-16) | | 9+8(x+3)= | | 15+4[m-2]=21 | | 2(x+8)=x+5 | | (D^4-5D^3+5D^2+5D-6)y=0 | | -42+8v=6+10(v-7) | | -x-1=-16 | | -152+-160-10x=-110-132x | | 4z-6=6(z+8) | | .5=-.6j+j | | x(x-1)(2x+5)=0 | | 10-3x=-1-8x | | -4(8+5n)-7x=25 | | bc=8v-2v+42 | | 5h+2(m+1)=23 | | 8-4(3x-2)-8x= | | -3x+6(-3x-6)=-183 | | .5=-.6j+1j | | 6w+5[w-2]=23 | | p=5k+5w | | 10-2x-6-4x=7 | | (3x+15)+(2x+25)=180 | | 3x=-1+8x | | x=28-19x | | Wx+b=y | | 2+3[x+1]=17 |